Statistical Study of the Association between Shelter Canine Intakes and Euthanasia from 2001 to 2011 in Taiwan - Yen, I-Feng; Lin, Hsiu-I; Lan, Dang-Jie; Chang, Ting-Wei; Pan, Kai; Fei, Chang-Young (The Thai Journal of Veterinary Medicine, 2013)
บทคัดย่อ การศึกษาครั้งนี้ใช้การทดสอบความสัมพันธ์เพียร์สันเพื่อวิเคราะห์ความสัมพันธ์ทางสถิติระหว่างจำนวนของสุนัขในสถานสงเคราะห์ และจำนวนสุนัขที่ถูกการุณยฆาต จากสถานสงเคราะห์เทศบาลใน 20 มณฑล/เมืองในประเทศไต้หวัน ระหว่างปี ค.ศ. 2001-2011 ข้อมูล สถานพักพิงสัตว์ข้อมูลเป็นข้อมูลทางการโดยสภาการเกษตร ตามอำนาจของพระราชบัญญัติคุ้มครองสัตว์ในไต้หวัน จากมณฑล/เมืองใน ไต้หวันจำนวน 20 มณฑล ยกเว้น Hualien Penghu Keelung และ Chiayi ซึ่งถูกคัดออกจากการศึกษานี้เนื่องจากข้อมูลที่ไม่สมบูรณ์ เมื่อใช้การทดสอบความสัมพันธ์เพียร์สันเพื่อวิเคราะห์ข้อมูลของทั้ง 16 มณฑล/เมือง ในช่วงปี 2001-2011 จาก 16 มณฑล/เมืองไม่รวมเมือง ไทเปใหม่ พบมีความสัมพันธ์อย่างมีนัยสำคัญมากที่สุดระหว่างจำนวนสุนัขในสถานสงเคราะห์และจำนวนสุนัขที่ถูกการุณยฆาต (p < 0.001) โดยมีลักษณะความสัมพันธ์เชิงบวก ชี้ให้เห็นว่าจำนวนสุนัขที่ถูกการุณยฆาตขึ้นกับจำนวนสุนัขในสถานสงเคราะห์ ผลการวิจัยชี้ให้เห็นว่าการ ลดจำนวนการุณยฆาตอาจจะเริ่มจากการจำนวนสุนัขในสถานสงเคราะห์ คำสำคัญ : สถานสงเคราะห์สัตว์, สุนัข, การุณยฆาต, สุนัขในสถานสงเคราะห์, สุนัขจรจัด, ไต้หวัน Abstract This study used Pearson correlation test to analyze statistical correlation between shelter canine intake and number of dogs euthanized in municipal animal shelters in 20 counties/cities in Taiwan from 2001 to 2011. Data of animal shelters were official data provided by the Council of Agriculture, the competent authority of the Animal Protection Act in Taiwan. Among the 20 counties/cities in Taiwan, Hualien County, Penghu County, Keelung City, and Chiayi County were excluded from this study due to incomplete data. Pearson correlation test was used to analyze the data of other 16 counties/cities from 2001 to 2011. Among these 16 counties/cities, excluding New Taipei City, there was a very significant correlation between shelter canine intake and number of dogs euthanized (p < 0.001) and the correlation efficient of the result was positive. This suggested that the number of dogs euthanized was subject to shelter canine intake. The research findings suggest that to decrease the number of dogs euthanized, reducing the number of shelter canine intake is the way to start. Keywords : animal shelter, dogs, euthanasia, shelter canine intake, stray dogs, Taiwan